Endothelial dysfunction in HIV infection: experimental and clinical evidence on the role of oxidative stress - Margaritis, Marios (Annals of Research Hospitals, 2019)
The human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) pandemic remains a world-wide health issue despite tremendous advances in antiretroviral treatments. As people living with HIV grow older, the incidence of traditional ageing-related diseases, such as coronary artery disease (CAD), will rise. HIV infection itself independently confers increased risk of cardiovascular disease. One of the early stages in the atherosclerotic process is endothelial dysfunction, characterised by oxidative stress imbalance and reduced availability of nitric oxide (NO) in the vascular wall. HIV-1 is the HIV type responsible for the global epidemic. Clinical evidence shows that infection with HIV-1 is linked to endothelial dysfunction. Molecular in vitro and in vivo studies have shown that this is at least partially mediated by effects of HIV-1 cellular infection and HIV-1 proteins on the enzymatic sources of oxidative stress in the vascular wall. This article reviews recent clinical and experimental evidence on the association between HIV infection and endothelial dysfunction and discusses the molecular mechanisms via which the HIV virus and its proteins alter the oxidative balance in the vascular wall, leading to increased reactive oxygen species (ROS) generation and causing endothelial dysfunction.